1987
DOI: 10.1017/s0144686x00012290
|View full text |Cite
|
Sign up to set email alerts
|

Retirement Migration and its Consequences in England and Wales

Abstract: Analyses are presented of data from the Office of Population Censuses and Surveys (OPCS) Longitudinal Study; a record linkage study in which one per cent of the 1971 Census population has been followed up using routinely collected demographic data. The data set includes the 1981 Census records of sample members. The results show that between 1970-1 and 1980-1 there was a fall in migration in the retirement age groups. In both periods there were differentials in rates of migration, particularly between counties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…Nevertheless, of those aged 50-64 at the time of their move to the English study areas, 31% had incomes over £25,000, a considerably higher proportion than amongst the non-mobile population (20.5%). These findings, when combined with the household composition profile provided above, seem to suggest similarities between the pre-elderly migrant cohort and the socio-economic characteristics of elderly migrants (Grundy, 1987;Warnes, 1993).…”
Section: Socio-economic Characteristics Of the Samplesupporting
confidence: 54%
See 2 more Smart Citations
“…Nevertheless, of those aged 50-64 at the time of their move to the English study areas, 31% had incomes over £25,000, a considerably higher proportion than amongst the non-mobile population (20.5%). These findings, when combined with the household composition profile provided above, seem to suggest similarities between the pre-elderly migrant cohort and the socio-economic characteristics of elderly migrants (Grundy, 1987;Warnes, 1993).…”
Section: Socio-economic Characteristics Of the Samplesupporting
confidence: 54%
“…Warnes (1983a,b) and Rogers' (1992) collection of papers make important contributions to our understanding of the emerging mobility patterns and processes associated with these groups. The mobility patterns associated with post-retirement age groups have been examined (Grundy, 1987;Rees, 1992;Warnes, 1992Warnes, , 1993Warnes, , 1994Warnes, , 1996Ford, 1993;Glaser and Grundy, 1998;Burholt, 1999). However, it was Warnes (1992) who identified that moves by persons around retirement age (the 'young-old') within the UK have been amongst the most dynamic, and that their mobil-ity patterns differ significantly from those undertaken by older persons.…”
Section: Migration and The Retirement Transition Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…We do not assert that migration to France is wholly different from elderly moves to other nations or to long-distance moves within nations. For one thing, the common observation that elderly migrants are drawn from more advantaged segments of society is not in dispute (Grundy 1987). Likewise, while our investigation did not specifically address these issues, we have no reason to doubt that few think of retiring outside Britain (Law and Warnes 1982), that couples are more inclined to move longer distances than the never-married, widowed or divorced (Cribier and Kych 1992) and that there are age-related variation and temporal adjustments in elderly migration (Cribier 1980;Warnes 1992 a).…”
Section: Expectations On Migration Flowsmentioning
confidence: 99%
“…Fundamentally, we see distinctions in reasons for home changes, which are emphasised through differences in places of origin and destination, as well as in the use to which overseas properties are put. Stated briefly, elderly long-distance migration is characteristically portrayed as originating, disproportionately, in larger cities (Grundy 1987). Yet few elderly people migrate long distances.…”
Section: Expectations On Migration Flowsmentioning
confidence: 99%